DESIGNING TEACHING MATERIAL TITLED TAX ADMINISTRATION FOR SMKN 1 TANJUNGPINANG - Susanti Susanti; Veronica Veronica (ConCEPt - Conference on Community Engagement Project, 2022)
Covid-19 pandemic has been affecting all sectors of the economy and no exception for education sector. Since covid-19 pandemic, teaching and learning process has been carried out online. Online learning is a challenge for both teachers and students. Therefore, making teaching materials are aims for helping teachers of SMKN 1 Tanjungpinang to know more materials and question banks, easier for teachers to execute materials to students through powerpoints and videos, and increasing student interest in learning. Data collection techniques for making teaching materials are through books, official websites such as Online Pajak, Direktorat Jenderal Pajak (DJP), Klik Pajak, and materials from tax brevet. The result of the implementation of this report are teachers and students can easily access the materials that being taught, increase students' learning interest, and add more resources and deeper learning through question banks.